2014
DOI: 10.1007/s00464-014-4029-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraoperative fluids on hospital length of stay in laparoscopic bariatric surgery: a retrospective study in 224 consecutive patients

Abstract: The amount of intravenous fluids administered during laparoscopic bariatric surgery plays a significant role on hLOS and on the incidence of delayed wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The same relationship was found in our study; however, a multivariate analysis revealed that it was contributing less to the risk of prolonged LOS. Nossaman et al concluded that the volume of intravenous fluids administered during laparoscopic bariatric surgery significantly correlates to LOS and delays wound healing [ 37 ]. They showed that lower volumes of intraoperative fluid were significantly associated with longer LOS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same relationship was found in our study; however, a multivariate analysis revealed that it was contributing less to the risk of prolonged LOS. Nossaman et al concluded that the volume of intravenous fluids administered during laparoscopic bariatric surgery significantly correlates to LOS and delays wound healing [ 37 ]. They showed that lower volumes of intraoperative fluid were significantly associated with longer LOS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nossaman et al concluded that the volume of intravenous fluids administered during laparoscopic bariatric surgery significantly correlates to LOS and delays wound healing [ 37 ]. They showed that lower volumes of intraoperative fluid were significantly associated with longer LOS [ 37 ]. Contrary to that, we observed that patients who required larger amounts of intraoperative i.v.…”
Section: Discussionmentioning
confidence: 99%
“…При забезпеченні радикальної цист-ектомії в 166 хворих P. Wuethrich (2014) застосував інфузію зі швидкістю 3 мл/кг/год із утриманням су-динного тонусу норадреналіном у дозі 2 мкг/кг/год, яку протиставив інфузії зі швидкістю 6 мл/кг/год без використання вазопресорів [40]. V. Nossaman (2015) взагалі розподілив хворих за групами дуже просто: при рестриктивному режимі рідинної ресус-цитації пацієнти під час лапароскопічних операцій отримували не більше за 1750 мл рідини, а при лібе-ральному -понад 1750 мл [41]. В роботі ж M. Healy (2015), до якої увійшли результати лікування 504 хворих, які перенесли панкреатектомію, проведено аналіз відповідно до ефектів 3 режимів інтраопера-ційного рідинного забезпечення: рестриктивного (< 10 мл/кг/год), стандартного (10-15 мл/кг/год) та ліберального (> 15 мл/кг/год) [42].…”
Section: який режим рідинної ресусцитації можна назвати рестриктивнимunclassified
“…1) [1]. However, attainment of a recommended 'liberal' intravenous fluid hydration strategy during these procedures with median surgical times of 1.0 [0.9-1.1] hrs is difficult [1]. A post-hoc analysis of the duration of nil per os (NPO) revealed a statistically significant dose-response association on the incidence of eHLOS [1]; with the lowest projected incidence within the 2-5 hr NPO interval (10-12 %, Fig.…”
Section: P023mentioning
confidence: 99%
“…As NPO is associated with a state of compensatory dehydration [2], the primary purpose of this study was to examine the role of a shorter NPO interval (C2 hrs) on the incidence of eHLOS and to establish causality between these variables. Methods: Following IRB approval and established fasting guidelines for adult patients, 168 consecutive bariatric surgeries were analyzed following institution of a revised oral water ad libitum policy on the incidence of eHLOS when compared to the prior data set [1]. Categorical variables were presented as percentages with differences between the groups assessed using Chi-square or Fisher exact tests.…”
Section: P023mentioning
confidence: 99%